Facing the challenges of global agriculture today: what can we do about drought - Okono, A.; Monneveux, P.; Ribaut, J.M. (Frontiers Media, 2013)
It is estimated that the planet's demand for food and feed crops will almost double by 2050 (Foley et al., 2011). Globally, rainfed agriculture is practised in 80% of the total agricultural area and generates 62% of the world's staple food (FAOSTAT, 2011). Taking into consideration global water scarcity and increases in demand for non-agricultural uses of water, expansion of the area under irrigation in developing countries does not appear to be a realistic scenario to address the challenge of food security.